Transcranial sonography in Parkinson''s disease. (February 2009) - ŠŠkoloudíík, David; Báártováá, Petra; Herzig, Roman
Transcranial sonography (TCS) is able to image in B-mode infratentorial and supratentorial structures, and can be used for the diagnosis and differential diagnosis of various intracranial pathologies. The authors review the contribution of TCS in the diagnosis and differential diagnosis of Parkinson''s disease (PD). TCS can be used to evaluate changes of echogenicity and in the area of substantia nigra in PD. Hyperechogenic enlarged substantia nigra can be detected in approximately 90% of PD patients and also in approximately 10% of the healthy population as a marker of subclinical injury of the nigrostriatal system. Hypoechogenic nucleus raphe could be detected in PD patients with unipolar depression and this finding also correlates with incontinency. Evaluations of echogenicity of the thalamus, nucleus lentiformis, nucleus caudatus, nucleus dentatus and the cerebellum, and measurement of enlargement of the ventricular system, could be used for differential diagnosis of movement disorders. TCS is a quick, safe and noninvasive method and can be used for early diagnosis of PD.